Bacterial infections and cancer. (22nd October 2018) - van Elsland, Daphne; Neefjes, Jacques
Abstract: Infections are estimated to contribute to 20% of all human tumours. These are mainly caused by viruses, which explains why a direct bacterial contribution to cancer formation has been largely ignored. While epidemiological data link bacterial infections to particular cancers, tumour formation is generally assumed to be solely caused by the ensuing inflammation responses. Yet, many bacteria directly manipulate their host cell in various phases of their infection cycle. Such manipulations can affect host cell integrity and can contribute to cancer formation. We here describe how bacterial surface moieties, bacterial protein toxins and bacterial effector proteins can induce host cell DNA damage, and thereby can interfere with essential host cell signalling pathways involved in cell proliferation, apoptosis, differentiation and immune signalling. Abstract : Many bacteria directly manipulate their host cell in various phases of their infection cycle. This review describes how bacterial surface moieties, protein toxins and effector proteins interfere with essential host cell signalling pathways, thereby promoting cancer formation.